Differences in coronary flow reserve and flow-mediated dilation between plaque psoriasis and psoriatic arthritis. (3rd October 2022) - Ikonomidis, I; Pavlidis, G; Katogiannis, K; Kapniari, I; Theodoropoulos, K; Kountouri, A; Kostelli, G; Tsilivarakis, D; Thymis, J; Katsimbri, P; Parissis, J; Filippatos, G; et al.
Abstract: Background/Introduction: Psoriatic disease is associated with increased cardiovascular risk through mechanisms of inflammation and oxidative stress. Purpose: We aimed to investigate endothelial glycocalyx, coronary microcirculatory function and flow-mediated dilation in patients with plaque psoriasis and psoriatic arthritis. Methods: In 311 patients (mean age: 52±12 years) with psoriatic disease (185 with plaque psoriasis and 126 with psoriatic arthritis) and 150 controls with similar age, sex and atherosclerotic risk factors, we assessed: (1) Perfused boundary region (PBR) of the sublingual microvessels with a diameter 5–25μm using Sidestream Dark Field camera (Microscan, Glycocheck). Increased PBR indicates impaired glycocalyx integrity. (2) Coronary flow reserve (CFR) in the distal left anterior descending coronary artery, (3) Flow-mediated dilation (FMD) of the brachial artery, and (4) LV global longitudinal strain (GLS) using speckle-tracking echocardiography. Results: Compared with controls, patients with psoriatic disease had higher PBR (2.14±0.29 versus 1.78±0.25μm, p<0.001) and lower CFR (2.86±0.93 versus 3.39±0.68, p<0.001), FMD (6.97±3.9 versus 9.1±2.1, p<0.001) and GLS (−17.4±3.8 versus −21.9±1.5%, p<0.001). There was not significant difference between the two study groups (plaque psoriasis and psoriatic arthritis) in PBR (2.14±0.28 versus 2.14±0.31μm, p=0.990) and GLS (−17.2±3.9 versus −17.6±3.8%, p=0.297). Patients with psoriatic arthritis had more impaired CFR (2.75±0.85 versus 2.96±0.99, p=0.045) and FMD (5.45±3.2 versus 7.76±4, p=0.003) compared to patients with plaque psoriasis. Conclusions: Patients with psoriatic disease have impaired endothelial, vascular and myocardial function compared with controls. Coronary microcirculatory function and flow-mediated dilation are more affected in psoriatic arthritis compared with plaque psoriasis. Funding Acknowledgement: Type of funding sources: None.